(untitled) (Revista da Tulha, 2023)
This work aims to reinvestigate, organize and centralize translations of terms cited by researchers as related to the ancestry of “VIOLAS”: belted box chordophones, better known for being part of orchestras - the so-called “family of violins”, where they are “bowed” instruments, that is, played primarily by bow - but also chordophones of similar shape, “fingered” (played directly by the fingers or some objects popularly called plectrum, as guitar picks). It was observed that most scholars would have assumed that “viola” and its variations in different languages would have been just names of bowed instruments, among other inaccuracies repeated in a chain for centuries, so it would be necessary to point out these situations in order to subsidize new studies in several areas of Science. The developments were based on the Dialectical Methodology and the historical-social contexts were estimated from the oldest records found for each variation of names, in the main European languages, since Latin used at 2nd century BC. The database was created through extensive research of sources pointed out by different types of researches at different times. Among the main reasons for carrying out this kind of reinvestigation is to include in previous investigative equations new factors such as the possibility of the existence of fingered instruments in the records. The main processes carried out were: reanalyze translations most used in publications; observe changes and variations of names among the different languages and identify possible patterns over the period.